A new flavonol glycoside from the flowers of Hosta plantaginea with cyclooxygenases-1/2 inhibitory and antioxidant activities. Issue 11 (3rd June 2019) - He, Junwei; Huang, Xiaoying; Wang, Yaqi; Liang, Jian; Liu, Ronghua; Zhong, Guoyue; Yang, Li
Abstract: Hosta plantaginea was a traditional Chinese medicinal plants used to treat inflammatory and painful diseases with partial scientific validation. Solvent extractions followed by repeated chromatographic purification of the H. plantaginea flowers led to the isolation of one new flavonoid glycoside, hostaflavone A (1 ), together with one related known compound, kaempferol-3- O -sophoroside-7- O -glucoside (2 ), and their structures were elucidated on the basis of chemical and spectral evidence, as well as by comparison with literature data. Compounds1 and2 were evaluated for the anti-inflammatory activites against cyclooxygenases (COX-1 and COX-2) and DPPH free radical-scavenging activities in vitro . The results revealed that1 and2 exhibited significant COX-1 inhibition and moderate COX-2 inhibition compared to the reference celecoxib. Additionally, 1 and2 displayed insignificant antioxidant activities compared to the positive control L-ascorbic acid. Abstract :